Validation of the Weight Concerns Scale Applied to Brazilian University Students. (June 2015) - Dias, Juliana Chioda Ribeiro; da Silva, Wanderson Roberto; Maroco, João; Campos, Juliana Alvares Duarte Bonini
Highlights: We investigated the Portuguese version of the Weight Concerns Scale (WCS). Construct validity of the WCS was analyzed using a confirmatory factor analysis. The WCS showed adequate validity and reliability in Brazilian university students. WCS is a simple, short, precise, accurate instrument assessing body weight concern. Abstract: The aim of this study was to evaluate the validity and reliability of the Portuguese version of the Weight Concerns Scale (WCS) when applied to Brazilian university students. The scale was completed by 1084 university students from Brazilian public education institutions. A confirmatory factor analysis was conducted. The stability of the model in independent samples was assessed through multigroup analysis, and the invariance was estimated. Convergent, concurrent, divergent, and criterion validities as well as internal consistency were estimated. Results indicated that the one-factor model presented an adequate fit to the sample and values of convergent validity. The concurrent validity with the Body Shape Questionnaire and divergent validity with the Maslach Burnout Inventory for Students were adequate. Internal consistency was adequate, and the factorial structure was invariant in independent subsamples. The results present a simple and short instrument capable of precisely and accurately assessing concerns with weight among Brazilian university students.